Atomic source selection in space-borne gravitational wave detection. (21st June 2019) - Loriani, S; Schlippert, D; Schubert, C; Abend, S; Ahlers, H; Ertmer, W; Rudolph, J; Hogan, J M; Kasevich, M A; Rasel, E M; Gaaloul, N
Abstract: Recent proposals for space-borne gravitational wave detectors based on atom interferometry rely on extremely narrow single-photon transition lines as featured by alkaline-earth metals or atomic species with similar electronic configuration. Despite their similarity, these species differ in key parameters such as abundance of isotopes, atomic flux, density and temperature regimes, achievable expansion rates, density limitations set by interactions, as well as technological and operational requirements. In this study, we compare viable candidates for gravitational wave detection with atom interferometry, contrast the most promising atomic species, identify the relevant technological milestones and investigate potential source concepts towards a future gravitational wave detector in space.